Establishing a biogumus stimulator of the rice culture growth with a high effect of synergy (Journal of Geography and Environmental Management, 2017)
When creating an agro-meliorative fertilizer (AMU) with a high synergism effect against boric toxicosis of rice field soils, the principles of the “New technology of developing saline soils for rice culture (NTOZ)” were adopted, which was applied in large areas of the rice plantation of the Republic of Kazakhstan and abroad. This technology was used a combination of shredded rice straw (up to 5T/ha) and zinc sulphate (ZnSo4) at a dose of 200 kg/ha. Synergistic effect of this tool were apparent yield of rice up to 40 kg/ha in case of total loss of seedlings at 3-4 leaves stage. The aftereffect of this meliorant was 7-8 years in the first year of development. The proposed work is a further development of the way of dealing with boron toxicity. Navesnoy offered by us in this work, the AF straw as organic matter is replaced by the vermicompost and additionally introduced sodium metasilicate (Na2SiO3). The degree of synergistic effect of the complex was established through careful laboratory experiments, testing of each individual sostavlyalo funds and of the complex and of the two, and the three combined. The experience consisted of two blocks: a) the test of sodium tetraborate from 6 to 10 mg/kg soil; b) in parallel, for every dose of boron to act AF in doses received in original condition. The results show that the most effective action AF was on a dose of boron from 6 to 8 mg/kg soil, and from 9 mg/kg length of seedlings was insignificant, components of a few centimeters.